Sentinel lymph node imaging by a fluorescently labeled DNA tetrahedron - Kim, Kyoung-Ran; Lee, Yong-Deok; Lee, Taemin; Kim, Byeong-Su; Kim, Sehoon; Ahn, Dae-Ro (ELSEVIER SCI LTD, 2013)
Sentinel lymph nodes (SLNs) are the first lymph nodes which cancer cells reach after traveling through lymphatic vessels from the primary tumor. Evaluating the nodal status is crucial in accurate staging of human cancers and accordingly determines prognosis and the most appropriate treatment The commonly used methods for SLN identification in clinics are based on employment of a colloid of radionuclide or injection of a small dye. Although these methods have certainly contributed to improve surgical practice, new imaging materials are still required to overcome drawbacks of the techniques such as inconvenience of handling radioactive materials and short retention time of small dyes in SLNs. Here, we prepare a fluorescence-labeled DNA tetrahedron and perform SLN imaging by using the DNA nanoconstruct With a successful identification of SLNs by the DNA nanoconstruct, we suggest that DNA tetrahedron hold great promises for clinical applications. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: NANOPARTICLES; DELIVERY; ULTRASOUND